DICER1 mutational spectrum in intracranial CNS-Neoplasias: a review and a report from the CNS-InterREST GPOH Study Center - Manea, Selma; Fincke, Victoria E.; Frühwald, Michael; Sturm, Dominik; Zezschwitz, Barbara von; Johann, Pascal-David; Mucha, Marlena (Cancers, 2025)
DICER1 tumor predisposition syndrome is a genetic condition that increases the risk of developing certain cancer types. While thyroid tumors are the main tumors caused by this condition in adult oncology, children and adolescents with DICER1 germline mutations may suffer from a broader spectrum of tumors, including Sertoli-Leydig cell tumors, pleuropulmonary blastomas, embryonal rhabdomyosarcomas, and pineoblastomas. Although these diseases—many of which are hallmark tumors of DICER1 syndrome and rarely occur sporadically—have been known for several years, the more recent identification of DICER1 mutations in embryonal tumors with multilayered rosettes (ETMR) and DICER1-associated intra- and extracranial sarcomas has expanded the spectrum of tumor types potentially linked to DICER1 syndrome. This review sought to investigate the presence and characteristics of DICER1 mutations in rare CNS tumors and to discuss their potential implications for early recognition of DICER1-related syndromes. To address this, we conducted a comprehensive systematic literature review and analyzed data from our nationwide German database (CNS-InterREST) regarding these entities. When present, DICER1 mutation status, mutation type (somatic vs. germline), and localization within the gene were recorded. Demographic and clinical data—including age at diagnosis and tumor localization—were also evaluated where available. We found that the prevalence of DICER1 mutations in the cohort of ETMR patients included in the CNS-InterREST study was exceedingly low (1/31). The distribution of DICER1 mutations in patients with ETMR or intracranial sarcomas is comparable to that in other previously identified DICER1-mutant tumors. Our literature review demonstrates that within the 248 cases, which include three intracranial DICER1-mutated neoplasias and one reference group, most somatic mutations accumulate in the RNase IIIb domain, while germline mutations are usually evenly distributed throughout the gene. Overall, further research is necessary to unravel the cell-of-origin of the respective tumor types and whether other, hitherto undescribed, genetic factors may contribute to the development of ETMR and DICER1-associated intracranial sarcomas.